Foreign Body Response to Intracortical Microelectrodes Is Not Altered with Dip-Coating of Polyethylene Glycol (PEG) - Lee, Heui C.; Gaire, Janak; Currlin, Seth W.; McDermott, Matthew D.; Park, Kinam; Otto, Kevin J. (Frontiers in Neuroscience, 2017)
Poly(ethylene glycol) (PEG) is a frequently used polymer for neural implants due to its biocompatible property. As a follow-up to our recent study that used PEG for stiffening flexible neural probes, we have evaluated the biological implications of using devices dip-coated with PEG for chronic neural implants. Mice (wild-type and CX3CR1-GFP) received bilateral implants within the sensorimotor cortex, one hemisphere with a PEG-coated probe and the other with a non-coated probe for 4 weeks. Quantitative analyses were performed using biomarkers for activated microglia/macrophages, astrocytes, blood-brain barrier leakage, and neuronal nuclei to determine the degree of foreign body response (FBR) resulting from the implanted microelectrodes. Despite its well-known acute anti-biofouling property, we observed that PEG-coated devices caused no significantly different FBR compared to non-coated controls at 4 weeks. A repetition using CX3CR1-GFP mice cohort showed similar results. Our histological findings suggest that there is no significant impact of acute delivery of PEG on the FBR in the long-term, and that temporary increase in the device footprint due to the coating of PEG also does not have a significant impact. Large variability seen within the same treatment group also implies that avoiding large superficial vasculature during implantation is not sufficient to minimize inter-animal variability.